An improved analytical method to design CMUTs with square diaphragms - Rahman, Dr. Md. Mosaddequr; Hernandez, Jonathan A Reynoso; Chowdhury, Sazzadur Tanvir Ur Rahman (© 1986-2012 Institute of Electrical and Electronics Engineers Inc., 2016)
This article was published in the IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control [© 1986-2012 IEEE.] and the definite version is available at: http://doi.org/10.1109/TUFFC.2013.2632 The Article's website is at: http://ieeexplore.ieee.org/document/6489818/